2020
DOI: 10.3390/diagnostics10070477
|View full text |Cite
|
Sign up to set email alerts
|

A Vegan Athlete’s Heart—Is It Different? Morphology and Function in Echocardiography

Abstract: Plant-based diets are a growing trend, including among athletes. This study compares the differences in physical performance and heart morphology and function between vegan and omnivorous amateur runners. A study group and a matched control group were recruited comprising N = 30 participants each. Eight members of the study group were excluded, leaving N = 22 participants. Members of both groups were of similar age and trained with similar frequency and intensity. Vegans displayed a higher VO2max (54.08 vs. 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…One cross-sectional study confirmed the information by investigating the difference in heart morphology and function according to the vegan and omnivorous diets in amateur runners [ 59 ]. The results showed that vegans had better systolic function, determined by longitudinal strain (vegan:−20.5% vs. omnivore:−19.6%), and diastolic function in vegans, determined by higher E-wave velocities (87 cm/s vs. 78 cm/s), compared to omnivorous athletes [ 59 ]. Therefore, we can confirm that vegetarian diets may have a beneficial impact on cardiovascular function; however, we still need further investigation on endurance athletes.…”
Section: Popular Diets Applied To Improve Sports Performance In Enmentioning
confidence: 94%
See 4 more Smart Citations
“…One cross-sectional study confirmed the information by investigating the difference in heart morphology and function according to the vegan and omnivorous diets in amateur runners [ 59 ]. The results showed that vegans had better systolic function, determined by longitudinal strain (vegan:−20.5% vs. omnivore:−19.6%), and diastolic function in vegans, determined by higher E-wave velocities (87 cm/s vs. 78 cm/s), compared to omnivorous athletes [ 59 ]. Therefore, we can confirm that vegetarian diets may have a beneficial impact on cardiovascular function; however, we still need further investigation on endurance athletes.…”
Section: Popular Diets Applied To Improve Sports Performance In Enmentioning
confidence: 94%
“…Studies on vegetarian diets have suggested that these diets may improve endurance performance by increasing exercise capacity and performance, modulating exercise-induced oxidative stress [ 72 ], inflammatory processes including anti-inflammatory and immunologic responses [ 4 ], and upper-respiratory tract infections (URTI) [ 73 ], and providing better cardiovascular function [ 59 ].…”
Section: Popular Diets Applied To Improve Sports Performance In Enmentioning
confidence: 99%
See 3 more Smart Citations